1984
DOI: 10.1111/j.1365-2133.1984.tb06604.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient and persistent photosensitivity due to musk ambrette. Clinical and photobiological studies

Abstract: Musk ambrette caused contact photosensitivity in five patients. One patient showed transient light reactivity and four showed persistent light reactivity. Tests with artificial radiation were performed on normal skin without musk ambrette being added. All patients reacted abnormally to UV-B and three to UV-A. In particular the patient with transient light reactivity showed abnormal responses to UV-B and UV-A. The patients were not always aware of the role of sunlight in the development of their eruption and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that chronic contact dermatitis from Compositae allergens could stimulate the skin's immune system by promoting recognition of endogenous neoantigens induced within the skin by irradiation alone (17). The presence of sensitizations to other allergens, like lichens or fragrances, in patients with clinical features of photodermatitis, has also been previously reported (18, 19), and they could also play a role in the development of CAD. The presence of phototoxic polyacetylenes in Compositae plants has also been used to explain the unclear connection between abnormal reactions to UV light and Compositae allergy (20).…”
Section: Discussionmentioning
confidence: 56%
“…It has been suggested that chronic contact dermatitis from Compositae allergens could stimulate the skin's immune system by promoting recognition of endogenous neoantigens induced within the skin by irradiation alone (17). The presence of sensitizations to other allergens, like lichens or fragrances, in patients with clinical features of photodermatitis, has also been previously reported (18, 19), and they could also play a role in the development of CAD. The presence of phototoxic polyacetylenes in Compositae plants has also been used to explain the unclear connection between abnormal reactions to UV light and Compositae allergy (20).…”
Section: Discussionmentioning
confidence: 56%
“…Most patients with TCSA-induced photodermatitis improved within a few weeks of allergen avoidance, but some patients developed persistent photosensitivity, with recurrent flares of dermatitis in sunlight despite the absence of TCSA, which was removed from soaps by October 1960 (4). Subsequently, more cases of PACD caused by other photoallergens like olaquindox and musk ambrette were reported (5)(6)(7)(8)(9). Although persistent light reactivity was also reported with other agents including musk ambrette, hexachlorophene, olaquindox, and ketoprofen (10,11), this entity is now considered a part of CAD spectrum (12)(13)(14)(15)).…”
Section: Historymentioning
confidence: 94%